2022
DOI: 10.1093/nar/gkac810
|View full text |Cite
|
Sign up to set email alerts
|

The yeast 2-micron plasmid Rep2 protein has Rep1-independent partitioning function

Abstract: Equal partitioning of the multi-copy 2-micron plasmid of the budding yeast Saccharomyces cerevisiae requires association of the plasmid Rep1 and Rep2 proteins with the plasmid STB partitioning locus. Determining how the Rep proteins contribute has been complicated by interactions between the components. Here, each Rep protein was expressed fused to the DNA-binding domain of the bacterial repressor protein LexA in yeast harboring a replication-competent plasmid that had LexA-binding sites but lacked STB. Plasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…The dimer Rep1/Rep2 has been shown to associate with the plasmid STB sequence to promote partitioning during cell division and both STB and REP1/REP2 are required for the plasmid stability in host cell (McQuaid et al, 2019; Mereshchuk et al, 2022). We therefore tested whether the distribution of contacts along the genome was dependent on these partners by generating Hi-C data of cells with a 2µ plasmid mutants lacking either REP1 or the STB loci (Kikuchi, 1983; McQuaid et al, 2019) ( Methods ).…”
Section: Resultsmentioning
confidence: 99%
“…The dimer Rep1/Rep2 has been shown to associate with the plasmid STB sequence to promote partitioning during cell division and both STB and REP1/REP2 are required for the plasmid stability in host cell (McQuaid et al, 2019; Mereshchuk et al, 2022). We therefore tested whether the distribution of contacts along the genome was dependent on these partners by generating Hi-C data of cells with a 2µ plasmid mutants lacking either REP1 or the STB loci (Kikuchi, 1983; McQuaid et al, 2019) ( Methods ).…”
Section: Resultsmentioning
confidence: 99%
“…Chromosome integration of episomal plasmids contributed to improved growth and improved nerolidol/valencene production. In Hxk2p-depleted/ hxk2Δ background (Figures , , and D,F), proteomic data showed that Rep2p, a key factor for 2μ plasmid inherence, was not present in Hxk2p-depleted cells. However, the activities of the REP2 promoter (and the TEF1 promoter as a reference) and the levels of the Rep2-yEGFP fusion under the control of the TEF1 promoter were not dramatically impacted by HXK2 disruption (Supplementary Figure 12).…”
Section: Discussionmentioning
confidence: 99%
“…In principle then, an ARS-plasmid non-covalently linked to the RSC complex should be able to overcome mother bias and improve its equal segregation frequency. In order to test this possibility, we relied on a [repressor-operator]-based experimental design described previously for recruiting proteins to specific sequences on plasmids to follow their segregation (Kiermaier et al, 2009;Lacefield et al, 2009;Mereshchuk et al, 2022).…”
Section: Equal Segregation Of An Ars-plasmid Can Be Improved By Assoc...mentioning
confidence: 99%